Collaborative Cross mice and their power to map host susceptibility to Aspergillus fumigatus infection - Durrant, C; Tayem, H; Yalcin, B; Cleak, J; Goodstadt, L; Pardo-Manuel De Villena, F; Mott, R; Iraqi, F (2011)
The Collaborative Cross (CC) is a genetic reference panel of recombinant inbred lines of mice, designed for the dissection of complex traits and gene networks. Each line is independently descended from eight genetically diverse founder strains such that the genomes of the CC lines, once fully inbred, are fine-grained homozygous mosaics of the founder haplotypes. We present an analysis of 120 CC lines, from a cohort of the CC bred at Tel Aviv University in collaboration with the University of Oxford, which at the time of this study were between the sixth and 12th generations of inbreeding and substantially homozygous at 170,000 SNPs. We show how CC genomes decompose into mosaics, and we identify loci that carry a deficiency or excess of a founder, many being deficient for the wild-derived strains WSB/EiJ and PWK/PhJ. We phenotyped 371 mice from 66 CC lines for a susceptibility to Aspergillus fumigatus infection. The survival time after infection varied significantly between CC lines. Quantitative trait locus (QTL) mapping identified genome-wide significant QTLs on chromosomes 2, 3, 8, 10 (two QTLs), 15, and 18. Simulations show that QTL mapping resolution (the median distance between the QTL peak and true location) varied between 0.47 and 1.18 Mb. Most of the QTLs involved contrasts between wild-derived founder strains and therefore would not segregate between classical inbred strains. Use of variation data from the genomes of the CC founder strains refined these QTLs further and suggested several candidate genes. These results support the use of the CC for dissecting complex traits. © 2011 by Cold Spring Harbor Laboratory Press.